Guidelines for conducting biofeedback-enhanced QoE studies in mulsemedia-enhanced virtual reality - Silveira, Aleph; Raisamo, Roope; Spyridonis, Fotios; Covaci, Alexandra; Ghinea, George; Santos, Celso A. S. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2023: Proceedings of the 29th Brazilian Symposium on Multimedia and the Web, 2023)
This paper presents the conclusions drawn from an ongoing experiment investigating the performance, usability, and impact of multisensory stimuli in the virtual environment, with a focus on proposing guidelines for conducting biofeedback-enhanced Quality of Experience (QoE) studies in multimedia-enhanced Virtual Reality (VR). The study evaluated various devices, including the Polar H10 and Grove GSR for biosignal measurement and an EEG device for brainwave analysis. Concerns related to participant comfort were highlighted, such as discomfort caused by tight electrodes and difficulties in achieving consistent contact with the scalp. Ergonomic issues with Head-Mounted Displays (HMDs) were also identified, emphasizing the need for comfortable and immersive experiences. The paper recommends addressing these concerns through inclusive design and user-friendly adaptation of devices. The findings emphasize the importance of integrated devices and user-friendly design to enhance QoE and facilitate the adoption of biofeedback technologies outside of the lab. By following the proposed guidelines, researchers and developers can improve the immersive experience and advance the field of biofeedback in VR environments.